PG103 'Managing bystanders' in an emergency situation: practising through simulation. (10th November 2020) - Tanner, Melanie; Hamilton, Carrie; Orledge, Jack; Andrews, Sarah; Booth, Jane
Abstract : Introduction: A repercussion of the NMC standards (2018a) and the NMC code (2018b) is that educators are considering the best teaching style to maximise student understanding and retention. Our second year student nurses learn the skill of basic life support; we wanted to extend this learning, enabling them the opportunity to practice 'bystander skills', immersing them in an unexpected 'crisis'. The aim was for them to practice verbal/nonverbal supportive skills with distressed relatives, manage crowds during a crisis event, deescalate and attend to privacy, recognise the challenges of unfamiliar situations, and build confidence if unethical or unsafe practice is noted. Methods: The simulation suite changing-room was converted to a swimming pool changing-room. 25 students in each cohort became bystanders to the (unseen) collapse and resuscitation of a child, in a semi-closed room. Two trained actor-role players, one the grandmother of the child and one a bystander taking photographs, were embedded in the changing-room with the students. Self-selecting student(s) immediately stepped in to support the distraught relative and, as the scenario progressed other student bystanders challenged the indiscreet onlooker. Two concurrent scenarios ran in the same area, with stop-start, freeze-frame and feedback from student participants, actor-role players, the group, and the facilitators. Results: This simulation was highly evaluated by students. They stated that they were more confident in their abilities to 'stay calm' in providing comfort and in challenging behaviours; the support of peers in 'pause and seek advice' was invaluable. The practical application of this simulation, in everyday life, and as value to society, was recognised. Cross faculty academics, health professionals and educators external to the University, observed and became involved as 'onlooking bystanders'. Over 200 student nurses have taken active roles in this simulation, with a further 50 student paramedics and ODPs – none in their professional roles, all as 'lay bystanders'. Discussion: Our mantra of 'teamwork makes the dreamwork' was upheld. Multiple discussions (pre/post simulation) with technicians, actors, a breadth of academics and students supported the venture. The actors were carefully selected, trained for their specific roles and agreed to wear swimsuits. Their involvement in the debrief was vital; a relative's perspective and a vicarious bystander perspective. De-roling was essential for all as the content of the simulation could be deeply upsetting. References: Nursing & Midwifery Council (NMC), (2018a) Standards of proficiency for registered nurses. London: NMC. Available at: https://www.nmc.org.uk/standards/standards-for-nurses/standards-of-proficiency-for-registered-nurses/ Nursing & Midwifery Council (NMC), (2018b) The code: professional standards of practice and behaviour for nurses, midwives and nursing associates. [pdf] Available at: www.nmc.org.uk/globalassets/sitedocuments/nmc- publications/nmc-code.